River Channel Characteristics at Selected Ice Jam Sites in Vermont - Gatto,Lawrence W (1978)
The objectives of this investigation were to describe channel characteristics and geographic settings of ice jam sites from aerial photographic interpretation, to indicate which characteristics may be important in causing ice jams, and to suggest additional uses of aerial photographs. Aerial photographs were taken of 19 sites with a Zeiss RMK 15/23 aerial camera on 17, 19, and 21 April 1976. Uncontrolled photomosaics of each site were assembled and major river characteristics were delineated on the photomosaics. Characteristics described include: manmade structures, falls, rapids, changes in channel depths, channel islands, mid-channel shoals or bars, river bed material, river sinuosity, meanders, floodplain width, riparian vegetation, and types of development on the floodplain. River channel widths were measured from the photographs along rivers where ground truth data were available for comparison. Lengths of channel riffles and pools were measured along the rivers where variations in river depths were evident on the photographs. Seventy-nine percent of the sites have some form of flow control structure which causes a pool with a backwater condition of low velocity. The low flow condition in the pool allows a solid ice cover to form which impedes ice movement and initiates ice jams. Aerial photographs provide a regional perspective for evaluating channel characteristics at an ice jam site and for analyzing the geographic setting at each site during ice-free conditions. Photographs taken after ice jams have formed are useful in monitoring ice jam formation, in analyzing ice characteristics, and in documenting ice jam breakup and movement. (Author)